2014
DOI: 10.1186/1758-5996-6-50
|View full text |Cite
|
Sign up to set email alerts
|

The association of body mass index with the risk of type 2 diabetes: a case–control study nested in an electronic health records system in the United States

Abstract: ObjectivesObesity is a known risk factor for type 2 diabetes (T2D). We conducted a case–control study to assess the association between body mass index (BMI) and the risk of being diagnosed with T2D in the United States.MethodsWe selected adults (≥ 18 years old) who were diagnosed with T2D (defined by ICD-9-CM diagnosis codes or use of anti-diabetic medications) between January 2004 and October 2011 (“cases”) from an electronic health records database provided by an integrated health system in the Middle Atlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
145
1
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(170 citation statements)
references
References 31 publications
13
145
1
11
Order By: Relevance
“…For example, obesity has been closely linked to type II diabetes [17], and the notion that depression may have a u-curved association with BMI has been asserted previously [18] and is supported in the current study. Similarly, gastrointestinal disorders have been linked to both the obese [19] and underweight groups [20].…”
Section: Discussionsupporting
confidence: 80%
“…For example, obesity has been closely linked to type II diabetes [17], and the notion that depression may have a u-curved association with BMI has been asserted previously [18] and is supported in the current study. Similarly, gastrointestinal disorders have been linked to both the obese [19] and underweight groups [20].…”
Section: Discussionsupporting
confidence: 80%
“…Term 'overweight' in categorization of BMI was classified as the increased risk status that substantially increases lifetime risk of diagnosed diabetes (Meigs et al, 2006). Moreover, Ganz et al (2014), strongly correlated the levels of BMI with risk of being diagnosed with T2DM, as individual with higher BMI has higher risk of T2DM as compared with a lower BMI (Ganz et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly a study by Ganz M, et al found a positive association between BMI and a risk of type-2 diabetes mellitus. 8 In a study by Hopper M, et al significantly higher blood glucose levels were also found in women, high BMI, low fitness, and rapid weight gain groups. 9 But in a study by Higaki Y et al body mass index, the percentage of body fat, and waist-to-hip ratio in the borderline glucose tolerance group did not differ from those in normal glucose tolerance group.…”
Section: Anthropometrymentioning
confidence: 99%